Performance and visual arts-based programs for children with disabilities: a scoping review focusing on psychosocial outcomes. Issue 4 (13th February 2020) - Edwards, Brydne M.; Smart, Eric; King, Gillian; Curran, C. J.; Kingsnorth, Shauna
Abstract: Purpose: There is a growing movement in pediatric rehabilitation to understand how approaches addressing aspects beyond body function contribute to enhanced psychosocial well-being. Among such approaches is the use of creative arts. A scoping review was undertaken to synthesize the current literature on performance and visual arts-based programs and outcomes for children with disabilities. Methods: Data sources included CINAHL, MEDLINE, and PsycINFO. Eligible articles described programs involving performing or visual art activities in community and ambulatory care settings, delivered to children between 6 and 18 years with physical or developmental disabilities, and reported on at least one psychosocial outcome. Domains of interest included emotional, social, behavioral, physical, cognitive, and/or communicative functioning, which are known to impact well-being and participation. No limits were applied to study design. Results: Twelve articles using primarily case study and quasi-experimental designs were identified, encompassing an 11-year period. Most programs focused on theater as the central modality. A majority of papers addressed changes in physical, cognitive, and communicative function ( n  = 8), followed by social function ( n  = 6), emotional function ( n  = 5), and finally, behavioral function ( n  = 3). Across individual papers, diverse study designs, measures, and outcomes were examined with positive qualitative and/or quantitative findings noted across all domains. Conclusions: Within an emerging evidence base, arts-based programs show potential to positively impact psychosocial well-being and warrant further investigation with broader populations of children with physical and developmental disabilities. A greater emphasis on programmatic approaches and enhanced methodological rigor to establishing benefits is needed to advance understanding. Implications for rehabilitation: Pediatric therapists may wish to consider recommending arts-based programs for children with ASD, TBI, and other developmental disabilities given their potential in achieving psychosocial outcomes Arts-based programs in rehabilitation provide creative ideas (e.g., drawing, painting) and techniques (e.g., modeling, role-play), which may be incorporated into individualized or group-based therapy to promote psychosocial well-being Program evaluators and researchers are encouraged to adopt a programmatic approach to further explore how art activities facilitate psychosocial outcomes